2022
DOI: 10.1371/journal.pone.0262079
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and costs among high-need and frail Mexican American Medicare beneficiaries

Abstract: Objectives To examine Medicare health care spending and health services utilization among high-need population segments in older Mexican Americans, and to examine the association of frailty on health care spending and utilization. Methods Retrospective cohort study of the innovative linkage of Medicare data with the Hispanic Established Populations for the Epidemiologic Study of the Elderly (H-EPESE) were used. There were 863 participants, which contributed 1,629 person years of information. Frailty, cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Sleiman et al [ 24 ] found that lower-income patients had a higher COC in comparison to higher-income patients after RSA; however, they did not stratify their study population by ethnicity. Similar to our results, previous studies have reported that Hispanics had a larger hospital expenditure, but these studies did not look at Hispanics after large operations such as total joint arthroplasty [ 22 , 25 , 26 ]. It is speculated that the lack of insurance for Hispanics results in a higher cost of care, as we found that Hispanic patients were significantly less likely to have private insurance and Medicare coverage.…”
Section: Discussionsupporting
confidence: 90%
“…Sleiman et al [ 24 ] found that lower-income patients had a higher COC in comparison to higher-income patients after RSA; however, they did not stratify their study population by ethnicity. Similar to our results, previous studies have reported that Hispanics had a larger hospital expenditure, but these studies did not look at Hispanics after large operations such as total joint arthroplasty [ 22 , 25 , 26 ]. It is speculated that the lack of insurance for Hispanics results in a higher cost of care, as we found that Hispanic patients were significantly less likely to have private insurance and Medicare coverage.…”
Section: Discussionsupporting
confidence: 90%
“…Among Latinos generally, use of healthcare resources varies across subgroups due to insured status, primary language spoken, country of origin, and length of time lived in the U.S. [ 12 ] Studies among Mexican Americans found that frailty was associated with increased Medicare spending [ 24 ] and Mexican Americans who were pre-frail or frail had significantly higher risk for hospitalizations compared to those who were non-frail [ 25 ]. While Latinos share many cultural experiences, there are differences among Latino subgroups in important areas such as ethnic/racial backgrounds, acculturation, colonial influences, socioeconomic status, and health status.…”
Section: Introductionmentioning
confidence: 99%